1997
DOI: 10.1094/phyto.1997.87.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of Phytophthora infestans in Ecuador

Abstract: The population genetic structure of Phytophthora infestans in Ecuador was assessed from 101 isolates collected from 1990 to 1992 and 111 isolates collected in 1993. All isolates were analyzed for mating type and allozyme genotype. Both samples were dominated (>95%) by a clonal lineage (EC-1) defined from neutral markers: 90/100 genotype for glucose-6-phosphate isomerase, 96/100 genotype for peptidase, A1 mating type, and a previously unreported nuclear DNA fingerprint. The remaining isolates belonged to the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 19 publications
5
82
1
Order By: Relevance
“…One of the challenges for developing good differential mixtures for late blight management in Ecuador is the apparent high degree of specific virulence in the absence of selection (8). The cost of virulence in P. infestans may be low or negligible.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges for developing good differential mixtures for late blight management in Ecuador is the apparent high degree of specific virulence in the absence of selection (8). The cost of virulence in P. infestans may be low or negligible.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, an effort was made to isolate from tissue containing only one lesion. Isolation was done by trapping with potato tuber slices (Forbes et al, 1997) or with a selective medium (Oyarzun et al, 1998). Isolates were maintained for short periods on Rye A and Rye B medium (Caten and Jinks, 1968) at 18°C in the dark, and stored for longer periods on Rye A agar slants at 15°C with 12-h photoperiod.…”
Section: Pathogen Collectionmentioning
confidence: 99%
“…Three of these appear to be clonal lineages, each characterized by a particular mating type, mitochondrial DNA (mtDNA) haplotype, nuclear RFLP fingerprint and isoenzyme electrophoretic pattern. Each of the three lineages has been described in detail: EC-1 (Forbes et al, 1997), US-1 (Oyarzun et a1., 1998), and EC-3 (Adler et al, 2004). Another pathogen group was described as the EC-2 clonal lineage (Ordon˜ez et al, 2000) but we have since identified new genotypes of P. infestans similar to EC-2 but differing in mating type and mtDNA haplotype.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations